Chicana/Latina Feminist Critical Qualitative Inquiry: Meditations on Global Solidarity, Spirituality, and the Land. Issue 4 (December 2017) - Saavedra, Cinthya M.; Pérez, Michelle Salazar
In this article we take a journey into using Chicana/Latina feminisms as one way to unearth new possibilities for critical qualitative inquiry (CQI). We start by offering a brief overview of Gloria Anzaldúa's influence on Chicana/Latina feminism, focusing on how she has inspired researching and writing from within rather than about as a decolonial turn (Keating, 2015). We then venture into new imaginaries to pose questions that would lead us to ponder about global feminista solidarity, the spirit, and the land. Our hope is that these contemplations lead us on a path of conocimiento where we can put the broken pieces of our/selves back together again.